The Development of the Interpretation of the Qur'an Pattern Lughāwi and its Implications in Islamic Education - Mohamad Agus Jauhari (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This research aims to trace the historical development of lughawi tafsir since the early days of Islam, starting from the era of the Companions and Tabi'in, the period of codification of classical tafsir, to its development in the modern era, as well as examining its implications for contemporary Islamic education. The method used is qualitative research with a literature review approach. Data were obtained from three main sources: (1) classical books of lughawi tafsir such as al-Zamakhsari's Al-Kasyaf and al-Farrā'ān's Ma'āni al-Qur'ān, (2) contemporary literature that examines the linguistics of the Qur'an, such as Dukes' Arabic Semantic in Quranic Discourse, and (3) Islamic education curriculum documents from various institutions. Data collection techniques are carried out through documentation and data analysis using a historical approach. The results of the study show that Lughawi Tafsir makes a great contribution to the development of Qur'anic sciences, especially in the field of linguistics and Qur'anic Ulumul. This approach has been proven to strengthen students' linguistic analysis skills, as well as encourage the mastery of linguistic tools in understanding the Qur'an. In addition, Lughawi's interpretation also influences the development of an Islamic education curriculum that emphasizes an interdisciplinary approach. However, challenges arise in the form of limitations of methodological innovation and the gap between classical traditions and the needs of modern education. This study confirms the importance of revitalizing Lughawi interpretation in the design of relevant and contextual Islamic curriculums.